Social Mobility among Christian Africans: Evidence from Anglican Marriage Registers in Uganda, 1895-2011 - Felix Meier zu Selhausen; Marco H. D. van Leeuwen; Jacob L. Wiesdorf (African Economic History Network (AEHN), 2017)
This article uses Anglican marriage registers from colonial and post-colonial Uganda to investigate long-term trends and determinants of intergenerational social mobility among Christian African men. We show that the colonial era opened up new labour opportunities for our African converts enabling them to take large steps up the social ladder regardless of their social origin. Contrary to the widespread belief that British indirect rule perpetuated the power of pre-colonial African elites, we show that a remarkably fluid colonial labour economy actually undermined their social advantages. Sons of traditional landed chiefs gradually lost their high social-status monopoly to a new commercially-orientated and well-educated class of Anglican Ugandans, who mostly came from non-elite and sometimes lower-class backgrounds. We also document that the colonial administration and the Anglican mission functioned as key steps on the ladder to upward mobility, and that mission education helped provide the skills and social reference needed to climb it. These social mobility patterns persisted throughout the post-colonial era despite rising informal labour during Idi Amin's dictatorship.
Keywords: J62; N27; O15; 330; Anglican Church; Chiefs; Christian Missionaries; Idi Amin; Indirect Colonial Rule; Social Mobility; Uganda